Eugeni d'Ors, la literatura comparada... y sus errores - Martí Monterde, Antoni (Tropelías: Review of Literary Theory and Comparative Literature, 2008)
Eugeni d'Ors, la literatura comparada... y sus errores
Keywords: Eugeni D'Ors